2002
DOI: 10.1097/00000542-200202000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Clonidine for Prevention of Perioperative Myocardial Ischemia

Abstract: The meta-analysis suggests that perioperative clonidine reduces cardiac ischemic episodes in patients with known, or at risk of, coronary arterial disease without increasing the incidence of bradycardia. Therefore, these findings strongly justify planning and execution of a definitive study seeking the benefits of clonidine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
28
1
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(36 citation statements)
references
References 2 publications
2
28
1
5
Order By: Relevance
“…This is still a controversial issue, however some authors have compared the effect of clonidine to that of beta-blockers on myocardial protection [1][2][3]12 . In this study, clonidine presented a sedative effect similar to that of diazepam, with an autonomic control characteristic of alpha-2 agonists, thus decreasing myocardial work.…”
Section: Discussionmentioning
confidence: 99%
“…This is still a controversial issue, however some authors have compared the effect of clonidine to that of beta-blockers on myocardial protection [1][2][3]12 . In this study, clonidine presented a sedative effect similar to that of diazepam, with an autonomic control characteristic of alpha-2 agonists, thus decreasing myocardial work.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are confirmed and reinforced by a large body of literature. 12, 13,15,[49][50][51][52][53][55][56][57][58]67,69,70 Clonidine is a mixed alpha agonist drug possessing peripheral ␣1 and ␣2 activity as well as imidazoline agonist effects. In low doses it primarily produces central ␣2 effects.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Additional investigations have shown that clonidine pretreatment also increases skin temperature 16 and decreases the difference between fingertip and forearm temperatures. 17 These results suggest an increase in cutaneous blood flow.…”
mentioning
confidence: 98%
“…Eine einzige Metaanalyse zum perioperativen Einsatz von Kalziumkanalblockern zeigte in der Posthoc-Analyse eine reduzierte Inzidenz perioperativer Myokardinfarkte, allerdings auch eine erhöhte Inzidenz an Hypotensionen [14]. Die Datenlage für den α 2 -Agonisten Clonidin ist zwar positiv, aber bis auf eine kleine Metaanalyse ebenfalls dünn [10]. Eine Statintherapie sollte prä-operativ nicht unterbrochen werden, da auch dies eine Destabilisierung koronarer Plaques zur Folge haben kann [7].…”
unclassified